2021
DOI: 10.1037/fam0000851
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between parents’ sleep problems and harsh parenting.

Abstract: Toward better understanding the determinants of harsh parenting, the present study assessed prospective associations between mothers' and fathers' sleep problems and their harsh parenting toward their child using two waves of data. Children's gender was examined as a moderator of these associations. At the first wave, 257 families participated. Mean age was 36.15 years (SD = 5.70 years) for mothers, 39.78 years (SD = 7.54 years) for fathers, and 10.41 years (SD = 7.85 months) for children. The sample was diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Nocturnal awakening is usually less frequent in toddlers than infants, but most children in this age group have at least one weekly wake-up in which they inform their parents of the awakening 13 . When children have difficulty falling asleep, their parents also have difficulty sleeping [14][15][16] . Hospitalized children both physically and emotionally need the simultaneous presence of their parents when they are hospitalized, and in the presence of both of them, the child feels more relaxed and the parents play an important role in the child's life during hospitalization 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal awakening is usually less frequent in toddlers than infants, but most children in this age group have at least one weekly wake-up in which they inform their parents of the awakening 13 . When children have difficulty falling asleep, their parents also have difficulty sleeping [14][15][16] . Hospitalized children both physically and emotionally need the simultaneous presence of their parents when they are hospitalized, and in the presence of both of them, the child feels more relaxed and the parents play an important role in the child's life during hospitalization 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, not only does sleep quality predict parents’ functioning (e.g., Peltz et al, 2020), but it is also an important component of family functioning (Meltzer & Montgomery-Downs, 2011). Parental sleep supports parents’ capacities to handle the day-to-day challenges inherent in parenting (Sinai & Tikotzky, 2012), and the downstream consequences of poor parental sleep, such as frequent night-wakings, can ultimately impact their parenting behaviors and children’s functioning (Kelly et al, 2021; Pinquart, 2017). Notably, previous research has suggested that parenting and children’s behaviors appear to be bidirectional in nature (Pinquart, 2017; Schermerhorn & Cummings, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Results in a sample of 142 mothers of infants demonstrated that mothers' irregular sleep patterns were associated with poorer parenting quality (e.g., less emotional availability) at bedtime (Bai et al, 2020). Despite the focus on maternal sleep in this area of research, Kelly et al (2021) found that shorter sleep duration, reduced sleep efficiency, and more frequent night-waking episodes predicted higher levels of harsh parenting in fathers, but not mothers. Meta-analytic results strongly support sleep impairments' negative influence on a wide range of cognitive abilities, including working memory, episodic memory, and problem solving (Wardle-Pinkston et al, 2019).…”
Section: Parental Sleep and Parentingmentioning
confidence: 90%
See 1 more Smart Citation
“…Worse sleep quality, for example, is related to both heart disease in the adult population (Cappuccio et al 2011) and depression among parents (Park, Meltzer-Brody, and Stickgold 2013). Poor sleep quality is associated with more harsh parenting behavior (Kelly et al 2021), and worse daily sleep quality has been found to exacerbate the effects of chronic and daily stressors on daily negative parental mood (da Estrela et al 2018;Lillis et al 2018;Mihaila and Hartley 2018). Thus, improvements in sleep quality may have the potential to lead to longer-term improvements in family functioning and child well-being, such as more positive parent-child interactions, reduced parental stress, and improved child behavior.…”
Section: Discussionmentioning
confidence: 99%